2000
DOI: 10.1007/s004420000365
|View full text |Cite
|
Sign up to set email alerts
|

Response of the copper butterfly Lycaena tityrus to increased leaf nitrogen in natural food plants: evidence against the nitrogen limitation hypothesis

Abstract: This study examined the effects of increased leaf N in natural food plants on oviposition, preimaginal survival, growth, and adult size of the butterfly Lycaena tityrus. Female butterflies did not discriminate between leaves of high and low N content. In accordance with previous studies, we found higher growth rates and concomitantly decreased development times at a high N level. However, because of high pupal (and larval) mortality (overall 73.0%) as well as a reduction in adult size (by ca. 8%) this was, ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 40 publications
2
65
0
2
Order By: Relevance
“…Merckx and Van Dyck 2006), rather than by the recent evolutionary history of the populations inhabiting them. It is known, that availability and quality of foodplants affect morphology of adult individuals (Fischer and Fiedler 2000). In earlier research on the dryad we have demonstrated that xerothermic grasslands offer substantially more nectar sources, whereas wet meadows are generally better in terms of larval foodplant abundance (Kalarus et al 2013).…”
Section: Discussionmentioning
confidence: 91%
“…Merckx and Van Dyck 2006), rather than by the recent evolutionary history of the populations inhabiting them. It is known, that availability and quality of foodplants affect morphology of adult individuals (Fischer and Fiedler 2000). In earlier research on the dryad we have demonstrated that xerothermic grasslands offer substantially more nectar sources, whereas wet meadows are generally better in terms of larval foodplant abundance (Kalarus et al 2013).…”
Section: Discussionmentioning
confidence: 91%
“…Dit kan leiden tot de aanmaak van stikstofhoudende vraatwerende stoffen dan wel tot tekorten aan mineralen of essentiële aminozuren. Voor Bruine vuurvlinder is er ook experimenteel bewijs dat N-overmaat leidt tot hogere sterfte, vooral in het popstadium (Fischer & Fiedler, 2000).…”
Section: 5unclassified
“…Nutrient supplementation to rice plants enhanced BPH fitness and increased starvation tolerance through the improvement of its biological and ecological parameters (Lu and Heong 2009). Nitrogen (N) is regarded as an indicator of plant quality (Lu et al 2007), and its limitation is widely studied for different insects. The herbivores on Nenriched plants showed higher survival rate (Prestidge 1982;Wier and Boethel 1995;Huberty and Denno 2006;Lu and Heong 2009) with bigger body sizes (Kaneshiro and Johnson 1996;Jauset et al 2000;Huberty and Denno 2006), shorter developmental time (Fischer and Fiedler 2000;Huberty and Denno 2006), fewer instars (Wier and Boethel 1995), and higher fecundity (Rashid et al 2016b). Nitrogen supplementation causes vigorous plant growth (Rashid et al 2016a) that may enhance ecological fitness potential of BPH through improvement of insect microecology.…”
Section: Introductionmentioning
confidence: 99%
“…Host plant quality plays a major role in the population development of planthopper by influencing performance and fitness (Cook and Denno 1994). Factors such as habitats, morphological, and chemical components (sugar, nitrogen, amino acids, and semiochemicals) in host plants can alter fitness parameters of insects (Sogawa 1982;Fischer and Fiedler 2000). Organisms are likely to be more fit when the elemental composition of available food is in balance with their requirement (Boersma and Elser 2006).…”
Section: Introductionmentioning
confidence: 99%